Characterization of the Enterobacteriaceae-associated ROD21-like family of excisable genomic islands and study of excision in the pathogenicity island ROD21 - Piña Iturbe, Luis Alejandro (2021)
The results of this thesis expand the repertory of identified excisable genomic islands, presenting insights about their evolution, and provide a first approach to the understanding of the regulation of excision in the pathogenicity island ROD21. These findings may contribute to the better understanding of current and emerging pathogens such as Salmonella serovars, pathogenic E. coli and carbapenem-resistant K. pneumoniae ST258, among others.